1977
DOI: 10.1121/1.381545
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and central processes in selective adaptation of place of articulation in stop consonants

Abstract: Recent accounts of selective adaptation in speech perception have proposed that either one or two levels of processing are adapted. Most of the previous experimental results can, however, be accounted for by either type of model. In the present experiments, two aspects of the selective adaptation paradigm were manipulated. The spectral (frequency) overlap between adapting and test syllables was manipulated along with differences in interaural presentation (adapting in one ear, testing in the other). The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0
2

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 21 publications
(34 reference statements)
4
69
0
2
Order By: Relevance
“…Since selective speech adaptation is argued to depend on low-level acoustic factors (e.g., Sawusch, 1977), it is conceivable that the effect arises early during auditory processing. The possibility that lexical information penetrates early auditory processes is corroborated by interactive approaches that assume lexical influences on pre-lexical processing and the finding that a lexically induced change in perceived sound identity reduces the Mismatch Negativity (MMN) at ~200 msec after stimulus onset .…”
Section: -Recalibration As a Default State?mentioning
confidence: 99%
See 1 more Smart Citation
“…Since selective speech adaptation is argued to depend on low-level acoustic factors (e.g., Sawusch, 1977), it is conceivable that the effect arises early during auditory processing. The possibility that lexical information penetrates early auditory processes is corroborated by interactive approaches that assume lexical influences on pre-lexical processing and the finding that a lexically induced change in perceived sound identity reduces the Mismatch Negativity (MMN) at ~200 msec after stimulus onset .…”
Section: -Recalibration As a Default State?mentioning
confidence: 99%
“…Originally, it was thought to reflect a fatigue of some hypothetical 'linguistic feature detectors', but others argued that it reflects a shift in criterion (Diehl et al, 1978), or a combination of both (Samuel, 1986). Others however (e.g., Sawusch, 1977), showed that the size of selective speech adaptation depends upon the degree of spectral overlap between the adapter and test sound, and that most, if not all of the effect is auditory rather than phonetic. A similar conclusion was reached by Roberts and Summerfield (1981).…”
Section: -Introductionmentioning
confidence: 99%
“…There is now considerable evidence that phonetic categories have a fine-grained internal category structure, with some members of a category perceived as better exemplars than others (e.g., Kuhl, 1991;Massaro & Cohen, 1983;Samuel, 1982;Sawusch, 1977). Miller and Volaitis (1989) reported that a change in speaking rate alters this structure, shifting which members of a category are perceived as the best exemplars.…”
mentioning
confidence: 99%
“…That is, it would be necessary to create stimuli that either possessed completely noncontiguous spectrotemporal specifications but produced the same phonetic percept or possessed identical acoustics but were perceived as belonging to different phonetic categories. The first alternative can be approached by synthesizing the same stop consonant before vowels with radically different formant center frequencies (e.g., Bailey, Note 1), or in syllables representing the outputs of vocal tracts of different lengths such that the formant peaks of one align with the valleys between the peaks in the other (Sawusch, 1977), or in syllables in which contrastive information is carried on a formant present in one syllable but absent in the other (Bailey,Note 1).…”
mentioning
confidence: 99%